(untitled) (Our Nature, 2021)
The Lohore River is one of the important riverine ecosystems of Dailekh which support diverse aquatic communities. The present study was carried out to assess the fish diversity status with relation to environmental conditions in both to space and time. The survey was conducted at three different sampling stations in three different seasons. For the fish sampling, two cast nets of different mesh sizes were used, one having large mesh size of 2 cm, 6 m diameter and 6 kg weight and another having mesh size of 0.5 cm, 3 m diameter and 2 kg weight. Moreover, drag net and gill net were also used to collect the fish samples. A total of 11 fish species belonging to 2 orders, 3 families and 7 genera. Results from the similarity percentage analysis (SIMPER) suggested that fish species of Puntius gelius, Schizothorax plagiostomus, Tor chelynoides and Schistura sovana were major contributing species each contribute more than 9%. An analysis of similarity (ANOSIM) pointed that fish community structure in the Lohore River differ in spatial scale (p<0.01) but not in temporal scale (P>0.01). Water temperature, dissolved oxygen and water velocity was found as influential factors for fish species distribution.